Biological sample’s challenge on pharmacogenetic studies - Bota i Arqué, Alexandre (Acta Bioethica, 2004)
This work starts stating the great increase of pharmacological studies associated with pharmacogenetic studies without clear knowledge of their consequences. The first challenge is to find out whether pharmacogenetic studies have greater implications than the determination of routine parameters. We cannot obviate that genetics engenders special worries due to several factors, such as: technical language, lack of information, media simplifications and complexity. The second goal is to define which property rights researchers or sponsor companies have on biological samples and genetic data in pharmacogenetic studies.